2018
DOI: 10.1186/s40249-018-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal clustering analysis of tuberculosis in the mainland of China at the prefecture level, 2005–2015

Abstract: BackgroundTuberculosis (TB) is still one of the most serious infectious diseases in the mainland of China. So it was urgent for the formulation of more effective measures to prevent and control it.MethodsThe data of reported TB cases in 340 prefectures from the mainland of China were extracted from the China Information System for Disease Control and Prevention (CISDCP) during January 2005 to December 2015. The Kulldorff’s retrospective space-time scan statistics was used to identify the temporal, spatial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
5
55
0
2
Order By: Relevance
“…Many studies utilizing spatial temporal mapping suggest that the main guideline for selecting an optimal scanning window is reducing the overlapping areas, or that a single cluster should make up no more than 15% of the whole study area [28,29]. Moreover, previous research in China at the prefecture level found that 11% was the optimal parameter for spatial cluster sizes, so we analyzed the notification rate of SS + PTB setting the maximum sizes from 8 to 11% of the total population at risk by increments of 1% [18]. When the maximum size is set at 8 to 11%, there are fewer overlaps, and the biggest cluster covered no more than 15% of all the provinces.…”
Section: Analysis Of Spatial Variation In Temporal Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies utilizing spatial temporal mapping suggest that the main guideline for selecting an optimal scanning window is reducing the overlapping areas, or that a single cluster should make up no more than 15% of the whole study area [28,29]. Moreover, previous research in China at the prefecture level found that 11% was the optimal parameter for spatial cluster sizes, so we analyzed the notification rate of SS + PTB setting the maximum sizes from 8 to 11% of the total population at risk by increments of 1% [18]. When the maximum size is set at 8 to 11%, there are fewer overlaps, and the biggest cluster covered no more than 15% of all the provinces.…”
Section: Analysis Of Spatial Variation In Temporal Trendsmentioning
confidence: 99%
“…Spatial and spatiotemporal analysis of TB notification cases could provide crucial epidemiological information to guide interventions. In recent years, the geographical information system (GIS) and spatial statistics were used to detect the spatial characteristics of TB in China [14][15][16][17][18]. Several studies have demonstrated that TB is not randomly distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Scan statistics were widely applied in study topic related to TB [39][40][41][42][43], whereas, data aggregated into large scales of administrative regions may ignore the disease variation in small size of population, information lose lead to inaccurate and insensitive conclusion [44], these national-level researches could not preciously detect localized cluster on the resolution of province or prefecture [9,10,45]. Meanwhile, due to the stochastic scan statistics sensitive to parameters, the analytical results on high-resolution scan of county-level may not stable.…”
Section: Correlation and Hierarchical Clustering Analysismentioning
confidence: 99%
“…As an airborne disease, PTB epidemics influenced the transmission in geographical neighborhoods, disease hotspots were defined as high-risk clusters. Studies reported hotspots regions or high-risk clusters of TB in China by using spatial-temporal scan analysis [9][10][11][12][13][14], spatial-temporal distribution characteristics were illustrated at the national, provincial, prefectural, county-level or individual level in diverse time frames, all of which have shown the geographical and temporal heterogeneity of TB epidemic.…”
mentioning
confidence: 99%
“…Geospatial analytical methods, such as geographic information systems (GIS) and spatio-temporal scanning analysis, are effective tools for helping to achieve such understanding [12][13][14]. In China, there were some studies intended to reveal the spatio-temporal distribution characteristics of TB under province, or nationwide, however, less discussion on the temporal and spatial distribution of tuberculosis in Xinjiang in recent years [15][16][17][18]. Therefore, the main objectives of this study were to investigate the temporal trends and spatial patterns of the TB surveillance data of Xinjiang from 2013 to 2016 by epidemic characteristics analysis, spatial autocorrelation analysis and spatio-temporal scanning analysis.…”
mentioning
confidence: 99%